2011
DOI: 10.1007/s10059-011-0014-x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Data Unveil Highly Divergent Populations within the Genus Hynobius (Caudata: Hynobiidae) in South Korea

Abstract: Korean salamanders of the genus Hynobius are currently classified into 3 species, H. leechii, H. quelpaertensis, and H. yangi. To investigate the phylogenetic relationship of these species, we analyzed the partial sequence of mitochondrial cytochrome b gene (907 bp) of 197 specimens from 43 regions in South Korea. Of these specimens, 93 were additionally examined with 12S rRNA (799 bp). Based on the partial sequence of the mitochondrial cytochrome b gene and 12S rRNA, 89 and 36 haplotypes were defined, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…() showed that the gold‐spotted pond frog Rana plancyi chosenica has two genetically diverse clades in Korea. Three cryptic sub‐clades were identified for Korean salamanders (genus Hynobius ) based on geographical differences (Baek et al ., ). Three distinct phylogroups were also found for the Siberian chipmunk Tamias sibiricus of South Korea from mtDNA cytochrome b (cyt b ) sequences (Lee et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…() showed that the gold‐spotted pond frog Rana plancyi chosenica has two genetically diverse clades in Korea. Three cryptic sub‐clades were identified for Korean salamanders (genus Hynobius ) based on geographical differences (Baek et al ., ). Three distinct phylogroups were also found for the Siberian chipmunk Tamias sibiricus of South Korea from mtDNA cytochrome b (cyt b ) sequences (Lee et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, the Korean Peninsula is divided by geographical landscape barriers, leading to the emergence of several clades within Pelophylax chosenicus ( Min et al, 2008 ), Hynobius spp. ( Baek et al, 2011 ; Min et al, 2016 ) and Dryophytes japonicus ( Dufresnes et al, 2016 ), a consequence of allopatric divergence.…”
Section: Introductionmentioning
confidence: 99%
“…Over two decades, several new Hynobius salamander species have been discovered on the Korean Peninsula, a very small area on the southern tip of East Asia (Kim et al 2007;Baek, Lee, Lee et al 2011a;Baek, Lee, Song et al 2011b;Min et al 2016). Hynobius unisacculus is the fourth Hynobius species officially recorded on this peninsula after H. leechii, H. quelpaertensis and H. yangi (Baek, Lee, Lee et al 2011a;Baek, Lee, Song et al 2011b;Min et al 2016).…”
mentioning
confidence: 99%
“…Over two decades, several new Hynobius salamander species have been discovered on the Korean Peninsula, a very small area on the southern tip of East Asia (Kim et al 2007;Baek, Lee, Lee et al 2011a;Baek, Lee, Song et al 2011b;Min et al 2016). Hynobius unisacculus is the fourth Hynobius species officially recorded on this peninsula after H. leechii, H. quelpaertensis and H. yangi (Baek, Lee, Lee et al 2011a;Baek, Lee, Song et al 2011b;Min et al 2016). Upon a phylogenetic tree reconstructed based on cyt b and 12S rRNA, this species formed a single cluster with H. quelpaertensis among these three previously known Hynobius species (Baek, Lee, Lee et al 2011a;Baek, Lee, Song et al 2011b;Min et al 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation